Pengaruh Pendidikan Kewirausahaan Dalam Menumbuhkan Minat Mahasiswa Menjadi Wirausahawan - Hardi Utomo (Departement of Mathematics Education, 2023)
Advances in technology and science have contributed to encouraging entrepreneurial practices which in turn have led to various inventions of new products and services for consumers. This of course opens up new job opportunities, opens up new markets, and in the long term will be able to create business growth in various sectors. The purpose of this study is to describe and analyze facts with the right interpretation of efforts to improve student soft skills through entrepreneurship education. So, the most appropriate research approach is a qualitative approach. After attending entrepreneurship education, students generally have the courage and self-confidence to increase, are more confident and stronger to enter the world of entrepreneurship/business.